(untitled) (Journal of the College of Basic Education, 2025)
The commercial cities in our Arab world were scattered and flourished and known in the Arabian Peninsula from the north to the south and in different areas, just as the cities of the Levant and Mesopotamia flourished, and they had an important and significant role at the political and economic level wherever they are found because of the importance of their location as a trade line or its proximity to important cultural centers as well. On the fertility of its land, and it had an important role in supplying the population with various agricultural or industrial products, in addition to its importance as important commercial centers that included many markets in which many commercial activities took place between buying and selling and the accompanying transactions and providing the requirements of incoming merchants, and the city Sanaa is one of these cities that occupied part of the land of Yemen, and in the south of the Arabian Peninsula, the research aims to shed light on this city in terms of its origin, importance, general conditions, and what is its political impact on the area that it occupied, and the research was divided into several axes: First: the summary, second: the city of Sana’a in which the following axes came: its origin, name, location, climate, economic conditions, political conditions, social conditions, religious beliefs, third: conclusion, R. Fourth: A list of sources and references.